The use of tourist mobile applications by the Y generation - Werenowska, Agnieszka (Wykorzystanie aplikacji mobilnych w turystyce przez przedstawicieli pokolenia Y, 2018)
Today, mobile technologies have become an inseparable element of travel planning. They give travellers access to all necessary information on an ongoing basis from almost anywhere in the world. The largest group of application users on mobile devices are members of the young generation, in particular Y and Z. The practical goal of the article was to present the ways of using mobile applications in tourism by members of the Y generation. The analysis of the survey results indicated that two-thirds of the respondents used mobile applications to organize a trip, and the rest combined traditional and modern tools in order to achieve the highest efficiency. At the same time, 98.9% of respondents believed that mobile applications would take over a significant part of the tourism market or even dominate the market in the coming years along with the development of their quality and usability. Surveys were conducted among 94 users of these technological solutions and the research results are presented in descriptive and graphic form, and a characterization of the studied generation was also made
Informatyka Ekonomiczna = Business Informatics, 2018, Nr 2 (48), s. 86-92
Keywords: pokolenie Y; internet; Y generation; millennials; mobile applications; tourism; Milenialsi; mobilne aplikacje; turystyka